Inherited predisposition to colorectal adenomas caused by multiple rare alleles of MUTYH but not OGG1, NUDT1, NTH1 or NEIL 1, 2 or 3. Issue 9 (30th May 2008) - Dallosso, A R; Dolwani, S; Jones, N; Jones, S; Colley, J; Maynard, J; Idziaszczyk, S; Humphreys, V; Arnold, J; Donaldson, A; Eccles, D; Ellis, A; et al.
Abstract : Background: MUTYH -associated polyposis (MAP) is a recessive trait characterised by multiple colorectal adenomas and a high risk of colorectal cancer. MUTYH functions in the DNA base excision repair pathway and has a key role in the repair of oxidative DNA damage. Objectives: To assess the contribution of inherited variants in genes involved in base excision repair and oxidative DNA damage including MUTYH, OGG1, NEIL1, NEIL2, NEIL3, NUDT1 and NTH1 to the multiple colorectal adenoma phenotype. Methods: Inherited variants of MUTYH, OGG1, NEIL1, NEIL2, NEIL3, NUDT1 and NTH1 were sought in 167 unrelated patients with multiple colorectal adenomas whose family histories were consistent with recessive inheritance. These variants were also characterised in ∼300 population controls. Results: Thirty-three patients (20%) and no controls were MUTYH homozygotes or compound heterozygotes (ie, carried two mutations) and therefore had MAP. Eight different pathogenic MUTYH mutations were identified, of which four were novel. MAP cases had significantly more adenomas than non-MAP cases (p = 0.0009; exact test for trends in proportions) and presented earlier (p = 0.013; analysis of variance). Twenty-four protein-altering variants were identified upon screening of OGG1, NEIL1, NEIL2, NEIL3, NUDT1 and NTH1 . However, all combinations of two (or more) variants that were identified at an individual locus in patients were also seen in controls, and no variants were significantly over-represented (or under-represented) in cases. Conclusion: Multiple rare alleles of MUTYH are associated with autosomal recessive MAP, while OGG1, NEIL1, NEIL2, NEIL3, NUDT1 and NTH1 do not contribute significantly to autosomal recessive polyposis.